Utilisation of personal care services in Scotland: the influence of unpaid carers - Elizabeth Lemmon (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2018)
Unpaid carers may have an influence on the formal care utilisation of the cared for. Whether this influence is positive or negative will have important implications for the costs of formal care provision. The relationship between unpaid and formal care is of particular importance in Scotland, where personal care is provided for free by Local Authorities, to individuals aged 65+. The existing evidence on the impact of unpaid care on formal care utilisation is extremely mixed, and there is currently no evidence for Scotland. This paper is the first to investigate how the presence of an unpaid carer influences personal care use by those aged 65+ in Scotland, using a unique administrative dataset not previously used in research. Specifically, it uses the Scottish Social Care Survey (SCS) from 2015 and 2016 and compares Ordinary Least Squares (OLS), Generalised Linear Models (GLM), and Two-Part Models (2PM). The results suggest that unpaid care complements personal care services and this finding is robust to a number of sensitivity analyses. This finding may imply that incentivising unpaid care could increase formal care costs, and at the same time it points to the potential for unmet need of those who do not have an unpaid carer. Due to the limitations of the data, future research is necessary.
Keywords: I11; I12; J14; 330; unpaid; care; informal; formal; substitution; complementary; elderly